2014
DOI: 10.2478/bvip-2014-0086
|View full text |Cite
|
Sign up to set email alerts
|

Detection of classical genes and enterotoxins of Staphylococcus aureus isolated from raw milk in the south-east region of Poland

Abstract: The aim of the study was to investigate if the enterotoxigenic strains of S. aureus isolated from raw milk are able to produce staphylococcal enterotoxins (SEs) A -E. A total of 168 of S. aureus isolates from raw milk collected in the south -east region of Poland (Lubelskie Province) were tested for SE production by the ELFA, while multiplex PCR was applied for detection of enterotoxin genes (sea, seb, sec, sed, see). It was found that 20 (11.9%) out of 168 strains were positive for one or more classical SE ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Kuplulu, Sarimehmetoglu, and Celik () reported that 35 (16.4%) of 214 cheese samples were contaminated with enterotoxigenic staphylococci species in Turkey. Similar values were detected by Korpysa‐Dzirba and Osek (). It was found that 20 (11.9%) out of 168 S. aureus isolates were positive for one or more classical se genes.…”
Section: Resultssupporting
confidence: 89%
“…Kuplulu, Sarimehmetoglu, and Celik () reported that 35 (16.4%) of 214 cheese samples were contaminated with enterotoxigenic staphylococci species in Turkey. Similar values were detected by Korpysa‐Dzirba and Osek (). It was found that 20 (11.9%) out of 168 S. aureus isolates were positive for one or more classical se genes.…”
Section: Resultssupporting
confidence: 89%
“…Our findings are in agreement with the report of Ertas et al (21) for S. aureus counts and with the report of Dzirba -Korpysa W. and Osek J. (22) for the prevalence of enterotoxic strains S. aureus.…”
Section: Discussionsupporting
confidence: 94%
“…Because of their high stability, these enterotoxins maintain activity in the digestive tract after ingestion ( Fisher et al, 2018 ). According to reports, food poisoning caused by these five classical enterotoxins accounts for 95% of staphylococcal food poisoning (SFP) cases, while the remaining 5% of infections are related to newly discovered SEs ( Korpysa-Dzirba and Osek, 2014 ; Papadopoulos et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%